1989
DOI: 10.1111/j.1365-2621.1989.tb03067.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potassium Sorbate, Sodium Acetate, Phosphates and Sodium Chloride Alone or in Combination on Shelf Life of Vacuum‐Packaged Pork Chops

Abstract: Microbiological and some physical and chemical effects of treating pork chop surfaces with sodium acid pyrophosphate, a commercial phosphate blend, potassium sorbate and phosphate/sorbate/sodium acetate solutions, with or without sodium chloride, before packaging were studied in pork chops vacuum-packaged and stored at 2A"C for 10 weeks. All treatments containing potassium sorbate reduced (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…The inhibitory effect of LA on growth of LAB in leg meats was significant when compared with the effects of PS, especially at the beginning of the storage period. The effect of PS on LAB, which are generally resistant to antimicrobial treatments, has been shown by Elliot et al (1985) and Mendonca et al (1989). Results reported by Woolthuis et al (1984) from pork livers with LA treatment are in agreement with the results of this study.…”
Section: Total Mesophylic Aerobic Bacteriasupporting
confidence: 95%
“…The inhibitory effect of LA on growth of LAB in leg meats was significant when compared with the effects of PS, especially at the beginning of the storage period. The effect of PS on LAB, which are generally resistant to antimicrobial treatments, has been shown by Elliot et al (1985) and Mendonca et al (1989). Results reported by Woolthuis et al (1984) from pork livers with LA treatment are in agreement with the results of this study.…”
Section: Total Mesophylic Aerobic Bacteriasupporting
confidence: 95%
“…S), which were unable to grow throughout the 1Zweek experimental period in KSP-treated steaks. In contrast, Enterobacteriuceae in steaks from all other treatments and control reached values as high as log,, 5.5-6.0 colony-forming units (CFU)/cmZ after only 5 wk of refrigerated storage at 2-4"C. These results were in agreement with those in earlier studies by To and Robach (1980a,b) in turkey, by Kondaiah et al (1985), who successfully used sorbate/citrate/ acetate/NaCl mixtures as antimicrobials in fresh beef, and by Mendonca et al (1989), who tested the KSP treatment in pork chops and concluded that potassium sorbate was the inhibitory substance in the mix. In that study, potassium sorbate solutions, with or without phosphates, sodium chloride or sodium acetate were equally effective in inhibiting growth of Enterobacteriaceae and spoilage microorganisms in fresh, vacuumpackaged pork chops but had detrimental effects on meat color unless phosphates were present.…”
Section: Resultssupporting
confidence: 93%
“…Mendonca et al (1989) reported that inclusion of sodium chloride and sodium acetate was unnecessary in potassium sorbate-phosphate surface treatments in fresh pork for antimicrobial or color protection purposes.…”
Section: Resultsmentioning
confidence: 98%
“…Extension of storage life in ice in vacuum-packed and treated samples has been reported previously. 3,4,6 It was also observed that the sensory scores correlated well with TMAN, TBA and total plate counts, whereas, TVBN values were well within the limits, except for control vacuum-packed samples, indicating that there was no correlation with sensory scores.…”
Section: Resultsmentioning
confidence: 64%